Evaluación institucional de la red educativa Saracay de la parroquia Saracay, cantón Piñas, provincia de El Oro, periodo lectivo 2011-2012 y propuesta de un modelo educativo basado en la interdisciplinariedad y el buen vivir para impulsar el desarrollo regional. - Ortega Valdiviezo, Teresita de Jesús (2016)
Human society at present moments crosses crucial stages of change, deep processing, and is that to be competitive in a globalized world it is necessary that people have based on knowledge, this being essential to be free and survive in this conflict stage. However, for all this scaffolding of knowledge and skills has positioning in man, it is essential that educational organizations with their manager, teacher and student human talent evolve into a knowledge society, transformed with management practice and prospective leadership establishments intelligent educational.